Scientific Writing: Hands-on Workshop Analysis Among the Faculty of Medical Sciences (Medical Forum Monthly, 2020)
Objective: To analyze the pre and post hands-on workshop analysis of faculty members related to medical sciences regarding scientific writingStudy Design: Cross sectional analytical studyPlace and Duration of Study: This study was conducted at the faculty of Medical Sciences in Al-Tibri Medical College and Hospital, Isra University Karachi Campus from January 2020 to May 2020.Materials and Methods: After taken an ethical approval, total 50 number of faculty members of medical sciences were enrolled in research based work shop on the basis of convenient sampling. The workshop was conducted in three different phases and equally divides the faculty into groups. Before the workshop, the participants were given verbal consent and fill the pre-workshop questionnaire and after completion of hands-on workshop the similar questionnaire was filled by the participants. Now the pre and post workshop data was collected and presented in the form of frequency and percentage of response given by the participants and Chi-square test was applied to draw the significant difference between pre and post analysis. The level of significance was taken P=<0.05Results: The significant difference (P value <0.01) were analyzed through pre and post workshop analysis in all component of the questionnaire Conclusion: The study results revealed the significant difference in pre and post analysis of faculty members, they are lacking in quality when it comes to knowledge and writing skills in scientific writing, however, if workshops are conducted regularly they will develop skills necessary to write better literature and submit their work in different publications for appraisal. Research excellence department should be established for the faculty development